2016
DOI: 10.1002/poc.3542
|View full text |Cite
|
Sign up to set email alerts
|

pH‐controlled reaction divergence of decarboxylation versus fragmentation in reactions of dihydroxyfumarate with glyoxylate and formaldehyde: parallels to biological pathways

Abstract: The reactions of dihydroxyfumarate with glyoxylate and formaldehyde exhibit a unique pH‐controlled mechanistic divergence leading to different product suites by two distinct pathways. The divergent reactions proceed via a central intermediate (2,3‐dihydroxy‐oxalosuccinate, 3, in the reaction with glyoxylate and 2‐hydroxy‐2‐hydroxymethyl‐3‐oxosuccinate, 14, in the reaction with formaldehyde). At pH 7–8, products (7, 8, and 15) exclusively from a decarboxylation of the intermediate are observed, while at pH 13–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
1
8
0
3
Order By: Relevance
“…meso -Tartrate was determined by comparison to the known literature. Pure glycolate was added to the NMR sample to confirm its location, and tartronate was assigned by comparison to previously published results …”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…meso -Tartrate was determined by comparison to the known literature. Pure glycolate was added to the NMR sample to confirm its location, and tartronate was assigned by comparison to previously published results …”
Section: Methodssupporting
confidence: 91%
“…Deprotonation effectively minimizes the orbital overlap between the delocalized carboxylate anions and the electron-rich ene-diol portion of the molecule. To the best of our knowledge, in cases where DHF behaves as an electrophile, the carboxylic acids of DHF existed as alkyl esters, whereas when the reacted as a nucleophile the carboxylic acid groups of DHF were always ionized using basic media. Even with this clear trend in the literature there has been no focused study on why seemingly minor changes to the carboxylic acid moieties of DHF have a profound effect on its reactivity. The relative stabilities of the DHF derivatives, especially toward reaction with atmospheric oxygen (to form dioxosuccinic acid) and self-condensation (via the putative keto form of DHF 2– to form sugar acid 5 , Scheme ) also seem to be affected by state of ionization of DHF versus its ester derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that reaction of glyoxylate 1 with catalytic cyanide at pH 13 led to the production tartrate 2 and oxalate 3 in high yields in a novel deoxalation reaction (Scheme a) . Within a prebiotic context, however, such a high pH could be considered problematic.…”
Section: Introductionmentioning
confidence: 99%